Effects of bio-insecticide formulated from M. charantia leaves extract in association with gum Arabic/kaolinite composite on mortality of Callosobruchus maculatus and nutritional composition of cowpea (Vigna unguilata) - Wangmene Bagamla; Bayang Jean Paul; Djakba Raphael; Ali Mahamat; Koubala Bargui Benoit; Harouna Massai (Journal of Agriculture and Food Research)
The preservation of post-harvest losses of cowpeas constitutes a major challenge for producers worldwide. Therefore, the aim of this work was to investigate the nutritional qualities of cowpea seeds treated with a bio-insecticide formulated from M. charantia leaves extract in association with gum arabic/kaolinite composite. Three bio-insecticides were formulated using different ethyl acetate, hexane and methanol solvents. These bio-insecticides were obtained by introducing each into a bottle, 10 g of composite in 10 mL of a solution (1 mg/L of extract each extract). However, 5 doses of each formulation (1 %–5 %) were prepared. Each dose of insecticide powders received 20 g of cowpea seeds and then infested with 10 C. maculatus previously starved for 48 h. Then, the biochemical parameters of untreated and treated cowpea seeds using the methanol formulation were evaluated. The obtained results showed that insecticide formulated at 5 % with methanol induced 100 % mortality rate on the second day of treatment with a lethal dose of 0.10 % which is related to its high content of triterpenes and polyphenols. The untreated (UWH) and treated (TWH) seeds without husk have the same contents of ash (2.19 %), proteins (29.14 %), fibers (2.69 %), vitamin C (147.32 mg/100 g) and carbohydrates (53.20 %), while untreated and treated seeds with husk showed the same values in these nutrients even for minerals content. Hence, biochemical analyzes of cowpea seeds treated with the formulated insecticide showed no change in nutritional quality and M. charantia leaves extract in association with gum arabic/kaolinite composite could be used as insect repellent.